Analisis Pemahaman Matematika Dalam Pembelajaran Menggunakan Multimedia Interaktif Pada Materi Segiempat - Paputungan, Insyirah; Mohidin, Abdul Djabar; Majid, Majid (Scimadly Publishing, 2023)
This study is a descriptive study aimed to describe the student’s mathematical understanding analysis in learning using interactive multimedia in the content of quadrangles to the 4th graders of SDN No. 98 Kota Utara. The research subjects comprised 4th graders students at SDN No. 98 Kota Utara, which amounts to 23 students. The techniques for collecting data in this research take the form of an 8-problem to expose. To measure how a student’s mathematical understanding is used 4 indicators include: (1) classifying objects according to certain qualities (according to the concept), (2) giving examples and non-examples of concepts, (3) restating a concept, (4) applying a problem-solving concept or algorithm. The study showed that the mathematics understanding of students in 4th grade in SDN No. 98 Kota Utara after learning through multimedia interactive was in enough category with a high percentage of 55.07%. As for the results of each indicator, obtained percentages, among others, are 60.87% for the first indicator and classified in the high category, 55.07% for the second indicator and classified in enough category, 63.77% for the third indicator and classified in the high category, and 43.84% for the fourth indicator and classified in enough category.